Time efficiency of catch landing using Sondong catcher at fish landing base Dumai City, Riau Province - M. Hariski; Muhammad Asshiddiqi; Adriani Adriani (Universitas Sam Ratulangi, 2022)
Efficiency is important in landing with the aim that the catch as soon as possible reaches the hands of consumers in good quality condition. Sondong fishing gear is a type of active fishing gear with an application process that is not too long so it is useful for maintaining the quality of shrimp because shrimp have organoleptic properties that rot quickly. The purpose of this study was to determine the efficiency level of landing time of catches using sondong fishing gear at the Fish Landing Base, Dumai City, Riau Province. The research was carried out at the Fish Landing Base, Dumai City, Riau Province, from June 5-25, 2021. The material in the research object was a sondong fishing boat, while the equipment needed was stationery, a stopwatch, a camera, and a laptop. The data collected are basic data, namely unloading time, effective time, wasted time, and supporting data, namely fleet size (GT), number of fish landed (kg), number of unloading personnel (people), and age of activity actors (years). The efficiency of the landing time of the catch using sondong fishing gear at the fish landing base in the city of Dumai is classified into the less efficient category, while the factors that influence fishing productivity are fishing experience, crew, and fishing time.